2015
DOI: 10.5222/head.2015.204
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Nursing Discharge Education Given By The Nurse With Patient Education Needs

Abstract: Bu çalışma, hemşirelerin hastaların taburculuk eğitim gereksinimlerine yönelik görüşleri ile hastaların gereksinim duyduğu taburculuk eğitim gereksinimlerine ilişkin görüşlerini karşılaştırmak amacıyla yapılmıştır. Yöntem: Tanımlayıcı ve kesitsel nitelikte olan çalışmanın evrenini 15 Eylül 2010-30 Nisan 2012 yılları arasında İstanbul'da özel bir hastanede yatarak tedavi olan ve çalışmaya katılmayı kabul eden 100 hasta ve bu hastalara taburculuk eğitimi veren hemşireler oluşturmuştur. Veriler, hasta ve hemşirel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 8 publications
1
3
0
2
Order By: Relevance
“…In the subscales of medications, life activities, feelings about the situation and treatment and complications, the information needs of the patients with high educational status were found to be high. 12 Accordingly, Tan et al (2013) found that patients with high educational status had a higher information needs in medications, life activities, treatment and complications subscales, which is similar to the findings of the present study. 10 When the means of the total scores and subscales of patients' professions and patient learning needs scale were compared, it was found that housewives had higher information needs in all subscales except medication dimension than the other groups.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In the subscales of medications, life activities, feelings about the situation and treatment and complications, the information needs of the patients with high educational status were found to be high. 12 Accordingly, Tan et al (2013) found that patients with high educational status had a higher information needs in medications, life activities, treatment and complications subscales, which is similar to the findings of the present study. 10 When the means of the total scores and subscales of patients' professions and patient learning needs scale were compared, it was found that housewives had higher information needs in all subscales except medication dimension than the other groups.…”
Section: Discussionsupporting
confidence: 90%
“…14 Yalcın state that patients with lower educational status had more information needs in all subscales of PLNQ. 12 According to the findings in the literature and the present study, it is expected that the general information needs of the patients with low education status are high. In the subscales of medications, life activities, feelings about the situation and treatment and complications, the information needs of the patients with high educational status were found to be high.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Bu eğitim etkinlikleri yalnızca hasta bireyi değil aynı zamanda ailesini ve yakınlarını da kapsamalıdır. (15) Hasta ve ailesinin eğitiminden sağlık profesyonellerinin bütün üyeleri sorumlu olmakla birlikte taburculuk planlaması özünde hemşirenin sorumluluğundadır. Hemşire hasta eğitiminde, bireyi komplikasyonlardan ve diğer sağlık sorunlarından koruyarak sağlığına kısa sürede ulaşmasını amaçlar.…”
Section: Taburculuk Eğitimiunclassified
“…Taburculuk eğitimi verilen hastaların iyileşme süreçlerinin hızlandığı, hastanelerin polikliniklerine tekrarlı başvuruların azaldığı ve buna bağlı olarak hasta bakım maliyetlerinin azaldığı, bakım kalitesinin yükseldiği belirtilmektedir. (15,16) Hasta Ebeveynlerine Verilen Eğitim Konuları Özellikle ülkemizde akraba evliliklerinin sıklığı ve geliştirilen yeni tanı yöntemleri ile tanımlanmış genetik hastalıkların sayısındaki yükseliş, hemşirelerin kliniklerde genetik hastalıklarla daha sık karşılaşmalarına neden olmaktadır. (17) Bu tür hastalıkların erken tanısı ve tedavisi hemşirelerin genetik hastalıklar yönünden bilgi donanımlarının yeterli ve farkındalık düzeylerinin yüksek olması ile olasıdır.…”
Section: Derleme • Reviewunclassified